Green gross domestic product: a bibliometric analysis - Karunanithi, Kriskkumar; Bui, Wency Kher Thinng; Tan, Houng Chien (John Wiley and Sons, 2024)
Green gross domestic product (GGDP) is a measure of economic performance that takes into account environmental aspects. This paper analyses the bibliographic data of 1321 articles retrieved from the Scopus database to shed some light on the GGDP literature for the past 47 years (1976–2022). Using VOSviewer, a combination of performance analysis (publication trend, top authors, top countries, top journals) and science mapping techniques (co-citation and co-occurrence) were employed. The co-citation analysis reveals three thematic clusters, namely: (1) political and social science dimensions of social and environmental reporting, (2) environmental disclosures, and (3) systematic review of social and environmental accounts. The co-occurrence analysis indicates a trend towards climate change and corporate governance, with a notable shift in focus from European and Eurasian countries to China. More importantly, this study offers valuable insights into the growing body of literature on GGDP, while emphasising the need for greater geographical representation and collaboration to advance the field.